The Effectiveness of Mental Toughness Training in Athletes: A Systematic Review and Meta-analysis - Lan, Jinyu; Ahmad Rashid, Rabiatul-Adawiah; Chen, Shancong (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to investigate the effectiveness of interventions targeting mental toughness (MT) in sport. Materials and Methods. Eligibility criteria encompassed quantitative controlled experimental studies of MT interventions in athletes. Information sources comprised studies indexed in Web of Science, PubMed, Scopus, Embase, and SPORTDiscus from inception to April 13, 2025. Reference lists of included studies were also screened. Risk of bias was considered as follows: Two authors independently assessed the reporting quality and risk of bias of included studies using a modified Downs and Black index. Regarding the synthesis of results, the standardized mean difference (SMD) was calculated to evaluate the effects of interventions using the random effect model. Results. This review included a total of 10 studies involving 465 participants, with sports primarily including soccer (24.7%), basketball (19.7%), and table tennis (17.5%). Seven studies (67.3%) employed a combination of psychological skills training interventions. The meta-analysis incorporated all 10 studies and their respective experimental groups to elucidate the overall efficacy of MT training programs. The pooled effect size was statistically and practically significant, yielding a large standardized mean difference of g = 0.81 (95% CI 0.57–1.05, p < 0.001), indicating a substantial advantage of MT training interventions over control conditions. Conclusions. This meta-analysis provides strong empirical evidence supporting the effectiveness of psychological interventions — particularly multicomponent Psychological Skills Training (PST) — in enhancing mental toughness among athletes across different sports. However, due to the lack of long-term follow-up assessments, reliance on quasi-experimental designs, and diversity in measurement approaches, the findings should be interpreted with caution. To advance the field, further research should adopt more rigorous methodologies, including large-scale randomized controlled trials and longitudinal designs, to identify the most effective components and delivery methods for developing mental toughness. These efforts will ultimately inform evidence-based practices for coaches, psychologists, and practitioners aiming to cultivate high-performing athletes.